2020
DOI: 10.1371/journal.pone.0240043
|View full text |Cite
|
Sign up to set email alerts
|

Exploring MRI based radiomics analysis of intratumoral spatial heterogeneity in locally advanced nasopharyngeal carcinoma treated with intensity modulated radiotherapy

Abstract: Background We hypothesized that spatial heterogeneity exists between recurrent and non-recurrent regions within a tumor. The aim of this study was to determine if there is a difference between radiomics features derived from recurrent versus non recurrent regions within the tumor based on pre-treatment MRI. Methods A total of 14 T4NxM0 NPC patients with histologically proven "in field" recurrence in the post nasal space following curative intent IMRT were included in this study. Pretreatment MRI were co-regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…The Pearson correlation coefficient was used to remove redundant features. LASSO regression was used for a further selection of the remaining features, which is consistent with most previous studies ( 10 12 , 18 , 19 ). Then, 20 MRI-radiomics that were most closely related to PFS tags were selected, and the importance of features in the model was sorted.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…The Pearson correlation coefficient was used to remove redundant features. LASSO regression was used for a further selection of the remaining features, which is consistent with most previous studies ( 10 12 , 18 , 19 ). Then, 20 MRI-radiomics that were most closely related to PFS tags were selected, and the importance of features in the model was sorted.…”
Section: Methodsmentioning
confidence: 92%
“…Farhan et al. found significant differences between recurrent and non-recurrent regions in seven features (including GLSZM) in the radiomics analysis of intratumoral spatial heterogeneity in LA-NPC ( 19 ). GLDM quantifies the dependence between the gray values of adjacent pixels and the gray values of central pixels within a certain distance, and its predictive value in NPC had been confirmed by Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of PET-MRI combined with radiomics, Feng et al ( 26 ) developed a radiomics model of FDG PET-MRI and reported areas under the curve (AUC) of the training group based on T2-weighted imaging and PET models of 0.85 and 0.84, respectively, and those of the validation group of 0.83 and 0.82, respectively, which offers great promise for the clinical staging of NPCs. In terms of internal heterogeneity of tumors, Akram et al ( 27 ) showed that the imaging features Neighboring Gray Tone Difference Matrix-busyness extracted from MRI data before and after treatment may reflect differences between recurrent and non-recurrent areas in tumors; moreover, they demonstrated the potential of radiomics in the identification of radiation resistance in tumors before treatment to select dose increments.…”
Section: Application Of Radiomics For the Diagnosis And Treatment Of Npcmentioning
confidence: 99%
“…In [ 99 ], the authors explored the issue of whether there was a difference between radiomic features derived from recurrent and non-recurrent regions within the tumour. Seven histogram features and 40 texture features were extracted from the MRI images of 14 patients with T4NxM0 NPC.…”
Section: Studies Based On Radiomicsmentioning
confidence: 99%